Supracrystalline Colloidal Eggs: Epitaxial Growth and Freestanding Three-Dimensional Supracrystals in Nanoscaled Colloidosomes - Yang, Zhijie; Altantzis, Thomas; Zanaga, Daniele; Bals, Sara; Van Tendeloo, Gustaaf; Pileni, Marie-Paule (Journal of the American Chemical Society, 2016)
The concept of template-confined chemical reactions allows the synthesis of complex molecules that would hardly be producible through conventional method. This idea was developed to produce high quality nanocrystals more than 20 years ago. However, template-mediated assembly of colloidal nanocrystals is still at an elementary level, not only because of the limited templates suitable for colloidal assemblies, but also because of the poor control over the assembly of nanocrystals within a confined space. Here, we report the design of a new system called "supracrystalline colloidal eggs" formed by controlled assembly of nanocrystals into complex colloidal supracrystals through superlattice-matched epitaxial overgrowth along the existing colloidosomes. Then, with this concept, we extend the supracrystalline growth to lattice-mismatched binary nanocrystal superlattices, in order to reach anisotropic superlattice growths, yielding freestanding binary nanocrystal supracrystals that could not be produced previously.